Multimarket contact and performance: Evidence from emerging economies - Beatriz Domínguez; Elisabet Garrido; Raquel Orcos (BRQ Business Research Quarterly, 2016)
The organizational structure of multinational enterprises (MNEs) is mainly made up of subsidiaries located in emerging and advanced countries. Consequently, they usually compete against the same rivals simultaneously in both emerging and advanced contexts. Multimarket contact (MMC) theory analyzes the competitive dynamics that arise in these situations. However, researchers have paid more attention to the consequences of multimarket contact in developed countries than to its effect in emerging countries. To explore the impact of the macroenvironment on the relationship between MMC and performance, we examine how coinciding with multimarket rivals in emerging economies alters the effect of MMC on firm performance. Our research, which is developed with a sample from the mobile telecommunications industry, shows that the presence of MNEs in emerging countries hinders the development of mutual forbearance practices and, therefore, reduces the positive effect of MMC on firm performance."
Keywords: 650; Multinational enterprises (MNEs); Multimarket contact (MMC); Emerging countries; Mutual forbearance and performance